Estimation of Atenolol and Nifedipine in Multicomponent Formulation by Ultraviolet Spectroscopy - Sachan, A. (Asian Journal of Chemistry, 2010)
Spectrophotometric methods requiring no prior separation have been proposed for simultaneous estimation of atenolol and nifedipine in two component tablet and capsule formulations. The methods employ first derivative spectrophotometry and ratio compensation technique for the simultaneous analysis of the two drugs. The absorbance maxima of atenolol was found to be at 276 nm and that of nifedipine was at 340 nm, in 50% v/v aqueous methanol. Atenolol and nifedipine obeyed Beer's law in the concentration ranges employed for these methods. Results of analysis and recovery studies were statistically evaluated for their accuracy and precision.